THE UNSTRUCTURED TRAP OF DIGITAL GOVERNANCE BIAS IN BREBES REGENCY, INDONESIA - Titi Rahmawati; Wahyuningrat Wahyuningrat; Muslih Faozanudin; Anggara Setya Saputra (Fakultas Ilmu Sosial Dan Politik, Universitas Wijayakusuma Purwokerto, 2025)
The Unstructured Trap of Digital Governance (UTDG) is a multi-disciplinary study that explains the phenomenon of poverty and development from the perspective of public administration, economics, and management. The UTDG grand design was prepared to explain and provide an overview of strategies in governance that enhance security and accessibility, on the other hand, it neglects the interests of economic and social adaptation for vulnerable communities. The difference in the functions and benefits of digitalization inherent in the concept of modernization actually causes the poor community to become increasingly trapped in conditions that render them more powerless. This study used a qualitative method for deep analysis besides various sources that have theoretical depth. The analysis of the results was processed through NVivo using a map. The data analysis of Nvivo represents the analysis of news and images regarding digital humanities, digital behavior, and digital territory in the Brebes Regency. Sampling was conducted using purposive sampling techniques. The research indicates that Brebes Regency falls into the fourth condition. The fourth condition reflects a gradual improvement in the government's digitalization efforts, reaching a relatively good level. Regulations have been established for digital-based public services, while adequate infrastructure is evidenced by the widespread distribution of internet access to even the most remote villages. However, several challenges persist, including low public awareness of digital literacy and internet addiction, where digital access is primarily used for social media rather than productive activities. This imbalance between the real and virtual worlds prevents digitalization from significantly improving societal welfare. Additionally, the economy continues to operate largely through conventional means, with few individuals actively participating as digital entrepreneurs. Instead, most remain passive consumers, serving as the target market rather than key players in the digital economy. As a result, despite moderate developmental progress, poverty levels remain high.